Influence of older generation's fertility behaviours on daughter's desired family size in Bihar, India - Abhishek Kumar; Valeria Bordone; Raya Muttarak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2014)
This paper investigates the associations between preferred family size of married women aged 16-34 in rural Bihar (India) and the fertility behaviours of their biological mother and mother-in-law. This information is based on scheduled interviews of 450 pairs of index women (i.e. women central in our analysis) and their mother-in-laws conducted in 2011. Preferred family size is first measured by Coombs scale, allowing us to capture latent desired number of children, and then categorized into three categories (low, medium, and hight). Ordered logistic regression is employed to estimate the preferred family size of index women. We find that family size preferences of index woman is not associated with grandchildren is positively associated with preferred family size of index woman and remains significant even after controlling for relevant socioeconomic characteristics. However, in the case where index woman has higher education than her mother-in-law, her preferred family size gets smaller. This suggests that education may provide women with greater autonomy in their decision making on childbearing.
Keywords: 300; coombs scale; desired family size; India; intergenerational transmission; mother-in-law